Etiology of Short Stature in Children Presenting At a Tertiary Care Hospital: Etiology of Short Stature in Children - Farooq, Arusa; Zaman, Qamar Uz; Nasir, Hina; Mukhtar, Nida; Siddique, Hira (Pakistan Journal of Health Sciences, 2025)
Short stature is frequently a rationale for consultation with pediatric endocrinology departments. It may arise from a multitude of origins, encompassing both physiological variations and pathological conditions. Objective: To ascertain the prevalence of various etiologies of short stature in pediatric patients attending a tertiary care medical facility. Methods: This cross-sectional study was carried out within the Pediatric Department of Shalamar Hospital, Lahore from August 2024 to February 2025. Subjects comprised 180 children exhibiting short stature as per operational definition, height falling beneath the 3rd percentile or two standard deviations below the mean corresponding to age and gender, included via non-probability consecutive sampling. Comprehensive history taking, physical assessments, anthropometric evaluations, and pertinent diagnostic tests were conducted. Data were analyzed using SPSS version 25.0 and various etiologies of short stature were presented as percentages and frequencies. Data were stratified by age, gender, residence, and socioeconomic status. Results: Familial Short Stature (FSS) constituted the predominant diagnosis among the pediatric population, impacting 20.6% of the subjects, followed closely by Constitutional Delay of Growth and Maturation (CDGM) and Primary Malnutrition, each accounting for 16.1%. Growth Hormone Deficiency (GHD) was identified in 15.6% of cases, while Hypothyroidism was present in 11.1%. Less prevalent etiologies included Celiac Disease (8.3%), Type 1 Diabetes Mellitus (T1DM) (7.8%), and Turner Syndrome, which affected 4.4% of the cohort. Conclusions: The main causes of short stature in children are familial and constitutional growth delay, along with endocrine disorders like hypothyroidism and growth hormone deficiency. Timely intervention is essential for optimal growth potential.